Pulmonary fibrosis as the sole manifestation of anti-Ku antibody positivity in the absence of myositis: A case report - Angelo Nigro, Dr. (Respiratory Medicine Case Reports)
Background: Anti-Ku antibodies are autoantibodies directed against the Ku protein complex involved in DNA repair. They are typically associated with overlap syndromes featuring polymyositis and systemic sclerosis. Isolated pulmonary involvement without myositis is exceedingly rare. Case presentation: We report the case of a 70-year-old male, a former smoker with an 18-year smoking history who quit 20 years ago, presenting with a one-year history of progressive dyspnea and dry cough. High-resolution computed tomography (HRCT) revealed pulmonary fibrosis with areas of ground-glass opacities. Laboratory tests showed antinuclear antibodies at a titer of 1:2560 with a speckled pattern and positivity for anti-Ku antibodies. Creatine phosphokinase levels were within normal limits. There were no clinical signs of myositis, myalgia, skin manifestations, or Raynaud's phenomenon. Conclusion: This case underscores the rarity of pulmonary fibrosis as the sole clinical manifestation associated with anti-Ku antibody positivity in the absence of myositis. Clinicians should consider testing for anti-Ku antibodies in patients with idiopathic interstitial lung disease, even when muscular and cutaneous symptoms are absent.